2010
DOI: 10.1165/rcmb.2008-0301oc
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immune Processes Are Sufficient for Driving Cigarette Smoke–Induced Inflammation in Mice

Abstract: The objective of this study was to characterize the impact of cigarette smoke exposure on lung immune and inflammatory processes. BALB/c and C57BL/6 mice were exposed to cigarette smoke for 4 days (acute) or at least 5 weeks (prolonged). Both mouse strains manifested an inflammatory response after acute smoke exposure, characterized by an influx of neutrophils and mononuclear cells. Multiplex analysis revealed a greater than twofold increase of the cytokines IL-1alpha, -5, -6, and -18, as well as the chemokine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
119
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(136 citation statements)
references
References 39 publications
14
119
1
2
Order By: Relevance
“…In contrast to the data presented in this study and the observations of others (16,35,36), there is some data suggesting that NK cells may be functionally suppressed in COPD. However, the interpretation of these reports is limited by small samples sizes, the use of non-COPD smokers with unknown patient characteristics, or in vitro treatment of PBMCs with Cs extract (55,56).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to the data presented in this study and the observations of others (16,35,36), there is some data suggesting that NK cells may be functionally suppressed in COPD. However, the interpretation of these reports is limited by small samples sizes, the use of non-COPD smokers with unknown patient characteristics, or in vitro treatment of PBMCs with Cs extract (55,56).…”
Section: Discussioncontrasting
confidence: 99%
“…Additional evidence implicating NK cells in the development of COPD comes from studies on immunocompromised mice exposed to CS (35,36). It has been demonstrated that, in the absence of T cells and B cells, the development of COPD phenotypes still occurred following chronic CS exposure (35,36). In addition, we have recently demonstrated a role for the innate functions of cytotoxic lymphocytes in the pathogenesis of COPD (6).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Details of the exposure protocol were reported previously (17). Average total particulate matter during exposure was 786 mg/L.…”
Section: Cs Exposure Protocolmentioning
confidence: 99%
“…2008; Botelho et al. 2010). We previously reported elevated levels of autoantibodies following 24 weeks of smoke exposure that persisted following smoking cessation, and coincided with the formation of TLT in the lungs (Morissette et al.…”
Section: Discussionmentioning
confidence: 99%